Triple Helix Collaboration: Optimising the Quality of Human Resources in the Digital Age through the Teaching Practitioner Programme - Pendriana, Yuli; Raharjo, Tri Joko; Pramono, Suwito Eko; Yulianto, Arief (Proceedings of International Conference on Science, Education, and Technology, 2024)
Changes in work patterns and trends in work skills needs caused by automation and increasingly sophisticated technology cause humans to be able to adapt quickly. It cannot be denied that there are changes in labor needs by the industrial world that must be responded to by higher education institutions. Higher education institutions are required to improve the quality of human resources to reach a superior level. In line with this phenomenon, this study aims to review how a government policy can encourage the integration of higher education, industry, and government to create quality human resources. The literature study method was used to obtain various information that became the focus of the study. The study results found that industry can encourage changes in government policy and demand innovation and transformation of higher education in producing superior resources as output by qualifications and needs. This study implies that universities, government, and industry have their respective roles and functions in the integration that encourages the birth of quality and superior human resources.